An approach to professional ethos in beginning psychology students centered into professional training - Pasmanik, Diana; Jadue, Fabiola; Winkler, María Inés (Acta Bioethica, 2012)
Between 2008 and 2010 the impact of four learning modules on the ethics of clinical and educational psychology was studied. In order to measure their effectiveness, before and after each intervention, -a filmed interview was presented related to each module and dramatized by actors- with ethical and technical errors. On the base of the responses given subjected to open and axial codification, correct and erroneous answers were analyzed, grouped by topics which showed the “stand” from which subjects answered. Realizing that this meant an approach to professional ethos, we analyzed part of the data with the aim to explore this ethos in 100 students, from three universities, which are starting their professional training cycle and which possess a different insertion of ethics training, organized in four groups and evaluated before being exposed to the modules.The results suggest that a professional ethos is being built with great convergences despite curricular differences.